PTU-049 Concurrent Immunomodulator Therapy does not Influence Infliximab or Adalimumab Trough Levels During Maintenance Therapy. (17th August 2016) - Bond, A; Fisher, G; Skouras, T; Subramanian, S
Abstract : Introduction: Combination therapy with infliximab (IFX) and immunomodulators (IM) is superior to monotherapy showing better outcomes at 1 year for Crohn's disease 1 and UC. 2 Withdrawal of IM after 6 months of combination therapy has been shown not to adversely affect clinical outcomes though patients on concurrent thiopurine have higher trough levels and lower CRP. 3 The role of concomitant IM therapy is unclear for patients treated with adalimumab (ADA). We aimed to evaluate the impact of concomitant IM therapy on trough levels of IFX and ADA. Methods: We conducted a retrospective observational study of all IBD patients on maintenance therapy who had had IFX and ADA trough levels measured between Jan13-Jan16. Testing was undertaken at the discretion of the treating clinician. Clinical information including duration of disease, site of disease, duration of anti-TNF therapy, IM therapy, smoking status, prior anti-TNF exposure, and disease activity was recorded. Drug level and anti-drug antibody measurements were performed on sera using the Lisa-Tracker IFX and ADA ELISA kit (Theradiag, France). Pairwise comparison of means was used to compare trough levels in patients with and without concomitant IM therapy. A multivariate logistic regression was used to correct for confounders and the impact on antibody formation assessed with Fishers exact test. Results: 200 patients (120 IFX and 80 ADA) were included. 65.8% of IFX and 55% of ADA patients were on concurrent IM therapy. Mean ADA trough levels among patients on concurrent IM was 6.72±1.91µg/ml whilst patients not on concurrent IM had levels of 5.16±2.88 µg/ml(p = 0.005). This difference was not significant after adjustment for dose escalation. 23 patients (28.7%) were on weekly dosing whereas 57 (71.2%) were on alternate weeks. The mean trough level in patients on IM was 4.01±3.52 and not on IM was 3.96±2.83(p = 0.9). Thirty patients had positive antibodies and trough levels were 1.25±2.1µg/ml compared to 4.91±3.1µg/ml(p < 0.001). The likelihood of developing antibodies was 26.8% without concurrent IM and 24% with concurrent IM (p = 0.82). Conclusion: Trough levels of IFX and ADA were not significantly different among maintenance patients with and without concomitant IM therapy. Surprisingly, the immunogenicity of IFX was not impacted by concurrent IM. References: 1 Ruffolo C, et al . Infliximab, azathioprine, or combination therapy for Crohn's disease. N Engl J Med 2010;363 :1086–8. 2 Panaccione R, et al . Combination therapy with infliximab and azathioprine is superior to monotherapy with either agent in ulcerative colitis. Gastroenterology 2014;146 :392–400. 3 Drobne D, et al . Withdrawal of immunomodulators after co-treatment does not reduce trough level of infliximab in patients with crohn's disease. Clin Gastroenterol Hepatol 2015;13 :514–21. Disclosure of Interest: None Declared